Hubungan Antara Obesitas Abdominal Dengan Kejadian Stroke Pada Penduduk Usia Dewasa Dan Paruh Baya : Tinjauan Literatur - Silalahi, Jessica Veronica; Ronoatmodjo, Sudarto (UI Scholars Hub, 2024)
Stroke is a major and growing global health problem. Stroke is a leading cause of illness and death worldwide and can be broadly classified as hemorrhagic stroke or ischemic stroke. There are many risk factors for stroke, including modifiable and non-modifiable risk factors. This study aims to investigate the correlation between central obesity and stroke incidence in adults and middle-aged using a systematic review. This study was conducted through a comprehensive search of several electronic databases, including Scopus, Science Direct, Proquest, and Google Scholar from June 2024 - September 2024. A total of 2,482 articles were screened based on the suitability of title, abstract, and type (original or non-original research). The remaining 549 articles were read in full text and entered into the data chart for identification, resulting in 8 articles that met the inclusion criteria for review. Data analysis included study identification, objectives, location (country), methodology (PEO and PRISMA-ScR flowcharts), and study findings. The study findings showed an association between abdominal obesity and stroke incidence and that body fat distribution is closely associated with cardiovascular disease incidence. Understanding the underlying mechanisms, risk factors, and management strategies is critical in reducing the impact of this widespread neurological condition.